Contemporary Treatment of Erectile Dysfunction A Clinical Guide - Köhler, Tobias S.; McVary, Kevin T. (Contemporary Endocrinology, 2016)
Now in a revised and expanded second edition, this comprehensive clinical guide remains a state-of-the-art synthesis of the literature, covering all aspects of treating erectile dysfunction (ED) and other related male sexual dysfunctions. Cardiovascular, hormonal, psychological and lifestyle factors are each considered in diagnosis and treatment, which includes pharmacological, surgical and prosthetic management strategies. The effects of prostate cancer and its treatment are also discussed, as are Peyronie's disease, priapism and ejaculatory disorders. New chapters in this edition discuss the profound effects of lifestyle change on sexual function, alternative and internet drugs that affect sexual function, endovascular approaches to ED, penile length considerations, the effect of radiation on erectile function, and optimizing ED research. Presenting a better understanding of what causes erectile dysfunction and the effective medications and non-medication treatments used to treat the condition, this invaluable title offers all physicians, residents, and fellows - and even medical students and other health professionals such as nurse practitioners and physician assistants - an essential reference for enhancing diagnosis and treatment of this common and debilitating disorder.